Coronal knee motion in children performing drop landings is not influenced by gender - Bauer, J. J.; Pavol, M. J.; Hayes, W. C.; Snow, C. M. (Annual Meeting of the American Society of Biomechanics. (Presented on poster September 9-10, 2004 at the ASB meeting in Portland), 2004)
Knee kinematics upon landing do not appear to be gender specific in pre-pubertal children, suggesting that the neuromuscular control of the limbs also does not differ. Neuromuscular training has been shown to eliminate gender differences in knee injury incidence in a young high-school population (Hewett, 1999). Therefore, neuromuscular training of girls before and during puberty might potentially prevent the development of any gender differences in mechanics that place women at greater risk of knee injury.